PENGARUH KOMPENSASI, KEPUASAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK BPD CABANG UTAMA DENPASAR - Ketut Agus Wira Adnyana; I Gede Rihayana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
An employee is said to have high performance, if the set workload is achieved and if the realization of work results is higher than that set by the company. Employee performance is very necessary, because with this performance it will be known how far their ability is in carrying out the tasks assigned to them. This research was conducted with the aim to determine the effect of compensation, job satisfaction, and work environment on employee performance at PT. BPD Bank Denpasar Main Branch. This research was conducted at PT. BPD Bank Denpasar Main Branch. The object of research in this study is compensation, job satisfaction, and work environment on employee performance at PT. BPD Bank Denpasar Main Branch. The population in this study were 63 employees of PT. BPD Bank Denpasar Main Branch. The sample in this study were 63 respondents who were determined based on the saturated sample method. Data collection was carried out through interviews and questionnaires. The analysis technique used in this study was multiple linear regression analysis which was processed using SPSS version 25 software. Based on the results of the analysis of this study, it shows that compensation has a positive and significant effect on employee performance at PT. BPD Bank Denpasar Main Branch. Job satisfaction has a positive and significant effect on employee performance at PT. BPD Bank Denpasar Main Branch. The work environment has a positive and significant effect on employee performance at PT. BPD Bank Denpasar Main Branch.